(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Diabetic nephropathy is one of the most serious complications of diabetes mellitus, leading to early disability and death of patients from end-stage renal failure [2, 12]. The prevalence of diabetic nephropathy is continuously increasing, which is associated with the interaction of genetic and environmental factors in patients with both type 1 and type 2 diabetes mellitus [1, 11]. The article discusses clinical and laboratory changes in patients with nephropathy in type 2 diabetes mellitus, assessed using laboratory tests [4, 6]. It has been established that the presence of even slight renal dysfunction in patients with type 2 diabetes mellitus can be diagnosed using laboratory tests [2, 7].